The urgency of resuming disrupted dog rabies vaccination campaigns: a modeling and cost-effectiveness analysis - Amber Kunkel (Nature Portfolio, 2021)
Abstract Dog vaccination is a cost-effective approach to preventing human rabies deaths. In Haiti, the last nation-wide dog vaccination campaign occurred in 2018. We estimated the number of human lives that could be saved by resuming dog vaccination in 2021 compared to 2022 and compared the cost-effectiveness of these two scenarios. We modified a previously published rabies transmission and economic model to estimate trends in dog and human rabies cases in Haiti from 2005 to 2025, with varying assumptions about when dog vaccinations resume. We compared model outputs to surveillance data on human rabies deaths from 2005 to 2020 and animal rabies cases from 2018 to 2020. Model predictions and surveillance data both suggest a 5- to 8-fold increase in animal rabies cases occurred in Haiti’s capital city between Fall 2019 and Fall 2020. Restarting dog vaccination in Haiti in 2021 compared to 2022 could save 285 human lives and prevent 6541 human rabies exposures over a five-year period. It may also decrease program costs due to reduced need for human post-exposure prophylaxis. These results show that interruptions in dog vaccination campaigns before elimination is achieved can lead to significant human rabies epidemics if not promptly resumed.